DIGITAL MARKETING STRATEGY IN FENOMENA CAFE OF THEMED SPORTS AND MUSIC IN SUPPORTING LOCAL CREATIVITY - Pierlita, Komang Yovansca; Mahmudah, Siti Muslichatul; Tresnawati, Yuni (Universitas Mercu Buana, 2025)
Digital marketing plays a crucial role in integrating digital technologies to attract customers, especially through social media. This study aims to analyze the digital marketing strategy implemented by Fenomena Café, a café with a unique sports and music theme, in supporting local creativity. The research applies the RACE model by Dave Chaffey as the analytical framework and employs a constructivist paradigm with a qualitative descriptive method. Data were collected from three key informants (owner and social media officer) and three additional informants from the Fenomena Café community.The findings reveal that Fenomena Café successfully increased brand awareness (Reach) and audience engagement (Act) through creative content on social media platforms, such as Instagram and TikTok. However, the optimization of the conversion stage (Convert) and personalization of interactions remains a challenge. This study suggests implementing additional strategies, such as storytelling content, loyalty programs, and chatbot technology, to enhance the effectiveness of their digital marketing strategy. These strategies are expected to strengthen Fenomena Café’s position as a creative hub while fostering stronger relationships with local communities.